The potential of the superoxide dismutase inhibitor, diethyldithiocarbamate as an adjuvant to radiotherapy - Kent, Charles (Division of Radiology, 2017)
It has long been known that oxygen has the potential to be toxic to biologic systems and that this toxicity is not due to oxygen itself, but due to the production of oxygen radicals. One of these potentially toxic radicals, superoxide (O₂⁻) can be generated as a result of ionizing radiation, and if not adequately removed can proceed to cause cell damage. Superoxide dismutase (SOD) is one of the key enzymes involved in the defence against oxygen toxicity. SOD activity can be inhibited by diethyldithiocarbamate (DOC), a powerful copper chelator. If inhibition of SOD by DOC increases the lifetime and effectiveness of radiation induced O₂⁻, it follows that the potential exists for DOC to enhance the effect of radiation. DOC is however also a thiol compound, and thus may act as a radioprotector by modifying tissue oxygenation status or by free radical scavenging. This study has concerned itself primarily with the inhibition of superoxide dismutase by diethyldithiocarbamate in order to sensitize tumours to ionizing radiation. The use of DOC as an inhibitor of SOD has however meant that any sensitization resulting from SOD inhibition could be masked by a radioprotective effect by DOC. The inhibition of SOD by DDC was confirmed in a murine rhabdomyosarcoma, and it was shown that this inhibition can be maintained for up to twenty-four hours after DDC administration. It was hypothesised that there was a potential for the radioprotective effect of DDC to be overcome, if the levels of DDC were low enough at the time of irradiation. Indeed, if DDC was removed from the growth medium of B16 mouse melanoma cells in culture prior to irradiation, a significant sensitization was demonstrated. It was shown that DDC could act as both a radiosensitizer and as a radioprotector in the same experiment. The dominant action of DDC was found to be dependent on the time allowed between DDC administration and irradiation. If this time was approximately 4 hours, it was possible to show a radiosensitizing effect by means of a tumour growth delay assay. This time modulation effect of DOC was shown in larger tumours, rather than smaller tumours, which could indicate that tumour oxygenation is an important criterion in determining the response to radiation of DOC treated cells. It was shown that B16 mouse melanoma cells exposed to 43°C after DDC pre-treatment were sensitized to thermal damage. This work suggests that some caution should be exercised when DDC is put forward as either a radiosensitizer or a radioprotector in the clinic, but that DDC may have potential as a thermosensitizer.